2011
DOI: 10.1111/j.1467-8691.2010.00585.x
|View full text |Cite
|
Sign up to set email alerts
|

Creativity‐Stimulating Leadership: A Critical Incident Study of Leaders' Influence on Creativity in Research Groups

Abstract: This study examines how group leaders in academic and industrial research settings stimulate creativity in group members. The study uses a modified version of the critical incident technique to collect creative incidents as perceived and reported in interviews with research group members. These incidents were content analysed according to the reported creative situation and the creativity-stimulating leadership behaviours. Reasons for the importance of the incidents are given (each incident is subdivided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 26 publications
(34 reference statements)
0
42
0
5
Order By: Relevance
“…Skill in handling interpersonal problems among members of an R&D project group is not something that R&D leaders have been formally trained (Elkins and Keller 2003). Despite calls for research that identifies the leadership needs of R&D professionals, a review of the literature shows that only a few studies have been conducted in R&D contexts (Elkins and Keller 2003;De Jong and Hartog 2007;Hemlin and Olsson 2011;. Still fewer studies have examined the validity of the identified leadership competencies by examining their relationships with employee attitudinal and performance indicators in R&D settings (Elkins and Keller 2003;Amabile, Schatzel, Moneta and Kramer 2004;Berson and Linton 2005).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Skill in handling interpersonal problems among members of an R&D project group is not something that R&D leaders have been formally trained (Elkins and Keller 2003). Despite calls for research that identifies the leadership needs of R&D professionals, a review of the literature shows that only a few studies have been conducted in R&D contexts (Elkins and Keller 2003;De Jong and Hartog 2007;Hemlin and Olsson 2011;. Still fewer studies have examined the validity of the identified leadership competencies by examining their relationships with employee attitudinal and performance indicators in R&D settings (Elkins and Keller 2003;Amabile, Schatzel, Moneta and Kramer 2004;Berson and Linton 2005).…”
Section: Introductionmentioning
confidence: 93%
“…Creativity scholars (e.g. De Jong and Hartog 2007;Hemlin and Olsson 2011; have called for a closer look at the leader behaviors that fundamentally address the nature of creative work. The apparent differences between the leadership requirements of traditional and empowered environments suggest that traditional measures of leadership may be, at most, only partially applicable to empowered team environments (Yukl 1999(Yukl , 2008Arnold, Arad, Rhoades and Drasgow 2000).…”
Section: Randd-specific Leader Behaviorsmentioning
confidence: 99%
“…Fourth, we propose that the sub-dimension of professional respect relates to creative performance. Professional respect is depending on expertise which is one of the central tenets for leadership of creative work (Hemlin & Olsson, 2011;Mumford, Scott, Gaddis, & Strange, 2002). Liden and Maslyn associate professional respect with autonomy, which is a characteristic of people who work in R&D (Feist, 2006).…”
Section: The Relationship Between the Lmx Sub-dimensions And Creativementioning
confidence: 98%
“…Management establishes cultural practices in an organization that can either foster or inhibit creative expression (Williams, 2001;Amabile et al, 2004;De Jong & Den Hartog, 2007;Gemünden, Salomo & Hölzle, 2007;Wang & Casimir, 2007;Byrne et al, 2009;Hülsheger, Anderson & Salgado, 2009;Isaksen & Ekvall, 2010;Hemlin & Olsson, 2011;Castro, Gomes & de Sousa, 2012). Management establishes cultural practices in an organization that can either foster or inhibit creative expression (Williams, 2001;Amabile et al, 2004;De Jong & Den Hartog, 2007;Gemünden, Salomo & Hölzle, 2007;Wang & Casimir, 2007;Byrne et al, 2009;Hülsheger, Anderson & Salgado, 2009;Isaksen & Ekvall, 2010;Hemlin & Olsson, 2011;Castro, Gomes & de Sousa, 2012).…”
Section: Introductionmentioning
confidence: 99%